Prosodical means applied in communicative relations - Aigul Murzinova, Kalima Yelshibaeva,; Koblanova, Aiman; Ainur Ansabayeva, Duisen Ansabayev, (Opción, 2019)
In modern society, the ability to speak beautifully and correctly is the criterion of a person’s success. Eloquence is the key to the social and economic development of a civilized society. Modern linguists pay special attention to an in-depth and comprehensive study of discourse. For the colourful sounding of the sentences during the speech, the clear and transparent sound and the precise transmission of the artistic features of speech, the speaker must perfectly master his speech apparatus. Only in this case the speaker can contribute to the formation and awakening of the aesthetic feelings of the listeners.